Biotin and arginine modified hydroxypropyl-β-cyclodextrin nanoparticles as novel drug delivery systems for paclitaxel. (15th July 2019) - Yan, Caixia; Liang, Na; Li, Qiang; Yan, Pengfei; Sun, Shaoping
Graphical abstract: Highlights: A novel biotin and arginine modified hydroxypropyl-β-cyclodextrin is synthesized. Based on this polymer, a paclitaxel-loaded nanoparticles system is developed. The paclitaxel-loaded nanoparticles are promising drug delivery carriers. Abstract: A novel biotin and arginine modified hydroxypropyl-β-cyclodextrin (biotin-Arg(pbf)-HP-β-CD) was successfully synthesized. The hydroxyl groups of HP-β-CD on the primary faces were coupled with carboxyl groups of biotin using arginine as the functional spacer. Using biotin-Arg(pbf)-HP-β-CD as the carrier, paclitaxel (PTX)-loaded nanoparticles were developed by modified emulsion solvent evaporation method. The optimized PTX-loaded biotin-Arg(pbf)-HP-β-CD nanoparticles had a mean diameter of 121.9 nm and zeta potential of -57.7 mV. Transmission electron microscopy (TEM) observation revealed that the nanoparticles were spherical in shape. XRD spectra confirmed the successful encapsulation of PTX. Moreover, in vitro and in vivo evaluations were performed to demonstrate the superior antitumor activity of the PTX-loaded nanoparticles. The cellular uptake study demonstrated the biotin receptor-mediated endocytosis of biotin-Arg(pbf)-HP-β-CD nanoparticles and the increase of cellular uptake by introduction of biotin and arginine. It can be concluded that the biotin-Arg(pbf)-HP-β-CD nanoparticles are efficient tumor-targeting drug delivery systems for PTX.